"My Teacher Had an Accent Too": Immigrant Teachers' and Counselors' Role in Multicultural Development—Perspectives of Multilingual Israelis. Issue 3 (October 2017) - Putjata, Galina
Transnational mobility across the world is opposed by a monocultural mind-set at school, which has led educational researchers across the world to call for a multilingual and multicultural turn. This article presents a qualitative study that investigates immigrant teachers' role in this transformation process. Framed by the specific historical context of Israel, where professional integration of new immigrant teachers was politically supported, the study focuses on biographies of Israelis, who had immigrated 20 years ago as children and youths. Their perception of immigrant teachers and counselors was reconstructed based on the theory of imagined community and school as linguistic marketplace. The findings allow deep insight into the process of identity construction and community imagining created by school as institution and immigrant teachers as its agents.